Anatomizing Civil War : Studies in Lucan's Epic Technique. - Dinter, Martin (Ann Arbor : University of Michigan Press, 2013)
Traces Lucan's epic technique.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books